Bentham or Aristotle in the Development Process? An Empirical Investigation of Capabilities and Subjective Well-being - Carol Lee Graham; Milena Nikolova (Institute for the Study of Labor (IZA), 2014)
Life evaluations and emotional states are distinct subjective well-being (SWB) components. We explore the relationship between opportunities and SWB dimensions, distinguishing between actual capabilities and means (education, employment, and income) and perceived opportunities (autonomy and health perceptions and belief in hard work). We find a link between capabilities and SWB (particularly, life evaluations), which varies across world regions. Capabilities can also be associated with stress and anger and seem to matter the least for the happiest respondents. We also explore the determinants of the least studied well-being dimension: eudaimonia, or life purpose, which is an underlying objective of the development process.
Keywords: I31; I39; 330; well-being; capabilities; freedoms; variance decompositions